Comparison of variables affecting the surgical outcomes of tubularized incised plate urethroplasty in adult and pediatric hypospadias. Issue 2 (April 2016) - Bhat, A.; Bhat, M.; Kumar, V.; Kumar, R.; Mittal, R.; Saksena, G.
Summary: Introduction: The American Academy of Pediatrics recommends operating on hypospadias between the ages of 6–12 months. Since most births in developed countries are conducted in a hospital, parents are likely to be well informed and counseled about the hypospadias. However, significant numbers of births in developing countries are still conducted at home, with illiteracy, poverty and ignorance often leading to late presentation at the hospital. Reported hypospadias-repair complication rates are higher in adults compared with those having surgery in childhood. The present study's objective was to evaluate the factors affecting surgical outcome in hypospadias patients undergoing tubularized and tubularized incised plate urethroplasty (TIPU) in adulthood compared with childhood. Materials and methods: A prospective study of 60 adult patients >16 years, and 60 pediatric patients <5 years who underwent TIPU for primary hypospadias between May 2008 and May 2012. Patients were operated on by a single surgeon, under similar circumstances, and were pre-operatively examined to assess meatal location, chordee, and torsion; they were also examined intra-operatively for quality of spongiosum and urethral plate width. The outcomes were assessed by patient/parents for satisfaction regarding cosmesis, urinary stream and complications. Results: The age of the patients varied from 16 to 27 years, with a mean of 20.8 years in adults, and 6 months to 5 years, with a mean of 2.1 years, in children. The type of hypospadias, degree of curvature, quality of spongiosum and urethral plate width were comparable in both groups, but complication rates were higher in adults (16.7%) than in the pediatric (6.7%) group (Figure 1 A–D). Meatal stenosis responded well to dilatation, but fistulae required revision surgery and had a cure rate of 100%. The median follow-up was 37 months in adults, and 39 months in children. Discussion: The higher complication rates in adults may be due to more frequent erections; increased susceptibility to infection along with relatively reduced vascularity lead to poor wound healing and increased complication rates. The limitation of the study was the small number of patients with mid and proximal hypospadias having lesser incidences in comparison with distal hypospadias. Adequate number of patients in these subgroups could have further strengthened the statistical correlation. Secondly, there was no objective criterion like uroflowmetry to assess urinary stream. Conclusions: Complication rates were higher in adults undergoing TIPU compared with pediatric patients, which was also statistically significant in distal hypospadias. The important factors in surgical outcome were: severity of hypospadias, degree of curvature, quality of spongiosum, and urethral plate width. Figure A. Bar diagram showing the effect of type of hypospadias on surgical outcome; B. the effect of chordee on surgical outcome; C. the effect of quality of spongiosum on surgical outcome; D. the effect of width of urethral plate on surgical outcome.